124k views
4 votes
Simplify the following expression

Simplify the following expression-example-1
User Wolf War
by
5.1k points

2 Answers

2 votes

Answer:

The answer is


4 {c}^(2) {d}^(2) √(10c)

Explanation:


\sqrt{160 {c}^(5) {d}^(4) }

To solve the expression, expand the terms

That's


\sqrt{ {4}^(2) * 10 {c}^(4) * {cd}^(4) }

Using the rule

The square root of a product is equal to the product of the roots of each factor.

Expand

That's


\sqrt{ {4}^(2) } * \sqrt{ {c}^(4) } * \sqrt{ {d}^(4) } * √(10c)

Reduce the surds

Thats


\sqrt{ {4}^(2) } = 4 \\ \sqrt{ {c}^(4) } = {c}^(2) \\ \sqrt{ {d}^(4) } = {d}^(2)

We have


4 * {c}^(2) * {d}^(2) * √(10c)

We have the final answer as


4 {c}^(2) {d}^(2) √(10c)

Hope this helps you

User Pretzel
by
5.0k points
2 votes

Answer:

See below

Explanation:

√160c⁵d⁴

= √160 * √c⁵ * √d⁴

= √16 * √10 * √c² * √c² * √c * √d² * √d²

= 4 * √10 * c * c * √c * d * d

= 4c²d²√10c

User Aleksei Poliakov
by
5.0k points